2011
DOI: 10.2807/ese.16.09.19806-en
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of syndromic surveillance in the Netherlands: its added value and recommendations for implementation

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The system also identifies diseases that are not being monitored, which may be new or re-emerging [24] . The primary results of a retrospective analysis by Wijngaard et al in 2010, based on the Dutch Healthcare register's symptom data, showed that among three syndromes, respiratory syndromes were the most closely associated with laboratory pathogen counts, with respiratory syndromes being 0-5 weeks ahead of laboratory influenza virus counts, indicating more timely and sensitive syndromic surveillance; on the other hand, gastrointestinal syndrome counts were 1-2 weeks ahead of laboratory rotavirus counts, while 62% of variants reported in neurological syndromes were caused by known viruses, suggesting that a proportion of unknown viruses were causing meningitis [25] . In 2009, Chinese academics conducted a laboratory-based symptom surveillance of patients in nine sentinel hospitals in Guangxi and discovered new infections caused by rare pathogens [26] .…”
Section: The Use Of Symptom Surveillance For Acute Emerging Infectiou...mentioning
confidence: 99%
“…The system also identifies diseases that are not being monitored, which may be new or re-emerging [24] . The primary results of a retrospective analysis by Wijngaard et al in 2010, based on the Dutch Healthcare register's symptom data, showed that among three syndromes, respiratory syndromes were the most closely associated with laboratory pathogen counts, with respiratory syndromes being 0-5 weeks ahead of laboratory influenza virus counts, indicating more timely and sensitive syndromic surveillance; on the other hand, gastrointestinal syndrome counts were 1-2 weeks ahead of laboratory rotavirus counts, while 62% of variants reported in neurological syndromes were caused by known viruses, suggesting that a proportion of unknown viruses were causing meningitis [25] . In 2009, Chinese academics conducted a laboratory-based symptom surveillance of patients in nine sentinel hospitals in Guangxi and discovered new infections caused by rare pathogens [26] .…”
Section: The Use Of Symptom Surveillance For Acute Emerging Infectiou...mentioning
confidence: 99%
“…10,11 Data collected from student or employee absenteeism have also been used to predict when outbreaks will occur several weeks earlier as compared to traditional surveillance and laboratory programs. 12,13 The goal of infection surveillance methods is to identify as many infected individuals as possible-as early on in infection as possible-and being able to accurately use this information to track and predict how infection will spread throughout the population.…”
Section: " "mentioning
confidence: 99%
“…Since the first publication on the emergence of Q fever in the Netherlands, thousands of cases have been reported [101,[107][108][109][110][111][112][113][114][115] and the study of small ruminants demonstrated that the same genotype C. burnetii identified in these animals was responsible for the epidemic of Q fever in the Netherlands [101]. Yet another study, conducted by Klaassen et al [116], identified five genotypes of C. burnetii in six patients and six animals from three different regions of the Netherlands [116].…”
Section: Q Fever and Coxiella Burnetii Diagnosis In Humansmentioning
confidence: 99%
“…Yet another study, conducted by Klaassen et al [116], identified five genotypes of C. burnetii in six patients and six animals from three different regions of the Netherlands [116]. Based on the Q fever epidemic occurred in the Netherlands, the application and importance of an efficient surveillance system, aimed at early identification, has been emphasized [101,113].…”
Section: Q Fever and Coxiella Burnetii Diagnosis In Humansmentioning
confidence: 99%